IMPLEMENTASI GURU KREATIF DAN INOVATIF ERA DIGITAL DI SMP PADA PEMBELAJARAN PJOK - Dea Firmansyah; Muhibuddin Fadli; Dea Firmansyah (Universitas Negeri Malang, 2024)
In the article the aim is to explore the implementation of creative and innovative teachers turning into a methodology for working on their expert capacity in computerized time. This article contains a presentation that understands the background to increasing correspondence and data innovation and its contents in the field of schooling. Then, this article understands the examination strategies used, by directing written surveys and investigations calculated to understand the creative and creative ideas and qualities of teachers relating to the computerized age. The results of the exploration show that imaginative and creative teachers provide important advantages in developing their skills. However, there are several difficulties that must be overcome in implementing imaginative and creative learning, for example limited assets, the need to further develop innovation capabilities, changes in learning standards, and adequate assessment. Overall, the use of imagination and development is an important stage in developing the expert capacity of teachers today. PJOK educators must have the ability to develop creative and innovative ideas, especially because not all institutions have adequate facilities. Therefore, PJOK educators must have good creativity and innovation so that the PJOK learning process can run effectively and smoothly.